Molecular cloning of DNA encoding a calmodulin-dependent phosphodiesterase enriched in striatum. - Polli, J W (1992)
A murine cDNA for the 63-kDa calmodulin-dependent phosphodiesterase (CaM-PDE), PDE1B-1, was isolated by using polymerase chain reaction with degenerate primers followed by the cloning of a full-length cDNA from a whole-brain phage library. The nucleotide sequence of 2986 base pairs contains an open reading frame encoding a protein of 535 amino acids (M(r) = 61,231) with a predicted isoelectric point of 5.54. The deduced protein sequence shows approximately 60% identity with that of the 61-kDa isoform (PDE1A2), consistent with the proposal that these proteins arise from two separate genes [Novack, J. P., Charbonneau, H., Bentley, J. K., Walsh, K. A. & Beavo, J. A. (1991) Biochemistry 30, 7940-7947]. Southern blot analysis suggests high nucleotide-sequence conservation of the PDE1B1 gene among mammalian and avian species. A single approximately 3600-nucleotide mRNA transcript was seen in all brain regions, with striatum containing 4- to 30-fold higher levels than other areas. In nonneural tissues, low amounts of PDE1B1 mRNA were detected in lung, spleen, thymus, and testis; hybridization to several larger mRNA species was also seen in thymus and testis. By using nucleic acid probes for PDE1B1, the mechanisms that control its highly selective gene expression can now be studied at the molecular level.